(untitled) (Annals of Medical Research, 2021)
Aim: This study aims to examine the outcomes of vitreoretinal surgery (VRS) in the treatment of cases detected to have posterior segment intraocular foreign body (IOFB) due to eye trauma. Materials and Methods: Files of patients who were detected to have posterior segment intraocular foreign bodies due to eye trauma and underwent VRS in our clinic between January 2014 and December 2018 were retrospectively reviewed. Patient age, sex, preoperative and final best corrected visual acuity (BCVA), initial eye examinations, nature of the foreign body and site of penetration into the eye, methods of foreign body removal, surgical methods, and complications were recorded. Results: Of the 16 patients included in the study, 15 (93.7%) were male and 1 (6.3%) was female. Mean age of the cases was 32.8±13.7 (14-58) years. Foreign body was metallic in 15 eyes, and a stone in one eye. Median time between trauma and IOFB removal was 3 days. Foreign bodies were removed via an enlarged sclerotomy in 13 eyes, and a limbal incision in 3 eyes. Visual acuity improved during postoperative follow-up in 12 patients, deteriorated in three patients, and remained unchanged in one patient. Mean initial BCVA of the cases was 1.54±0.57 logMAR and mean final BCVA was 1.03±0.6 logMAR (p=0.014). Four eyes demonstrated recurrent/new retinal detachment (RD), two eyes macular scaring, one eye a transient increase in intraocular pressure, one eye aphakia, one eye hemorrhagic choroidal detachment, and one eye phthisis bulbi. Median follow-up time was 14 (3-58) months. Conclusion: VRS is an effective and safe procedure for the removal of posterior segment intraocular foreign bodies; however, visual and anatomic outcomes can be affected by various factors in these cases. Macular scaring and a recurrent or new RD are associated with poor final visual outcomes.